Characterization of carcass bruises in cattle in Northern Portugal, a preliminary study. Issue 1 (1st January 2021) - Teiga-Teixeira, Pedro; Moura, Dina; García-Díez, Juan; Esteves, Alexandra
Abstract: The study of wounds in live cattle and carcass bruises can be used as welfare indicators at pre-slaughter stages (farm and transport). The knowledge about the aetiology for both wounds and bruises may develop strategies to reduce its prevalence, improve cattle welfare and decrease the economic losses related to partial condemnations. The current work assesses the presence of bruises in cattle carcasses. A total of 236 (51.08%) out of 462 cattle displayed bruises. Most bruises were small (46%), circular (26.8%)/irregular (48.9%), haemorrhagic (63.6%) and superficial (81.1%). The occurrence of bruises was influenced ( p < .01) by sex, age, breed, production (beef or dairy), body condition score, cleanliness, sex at lairage pens and lairage time. Transport time and distance influenced neither wounds nor bruises ( p > .05). From a practical point of view, the results of the current work highlight the role of farmers, personnel involved in cattle transport and slaughterhouse staff to control and optimise cattle welfare to decrease the occurrence of bruises. Because most bruising resulted from recent events, management measures, such as keeping cattle of the same sex, age, and body condition score in lairage pens, may decrease the occurrence and further economic losses associated with partial condemnations. HIGHLIGHTS: Occurrence of bruised carcass in cattle was over 50%. Most bruises were small, circular/irregular, superficial and recent. Sex and age were the largest risk factors of bruised carcasses. Assessment of carcass bruises can be used as a welfare indicator.